Turbomachinery flow physics and dynamic performance - Schobeiri, Meinhard T.
With this second revised and extended edition, the readers have a solid source of information for designing state-of-the art turbomachinery components and systems at hand.   Based on fundamental principles of turbomachinery thermo-fluid mechanics, numerous CFD based calculation methods are being developed to simulate the complex 3-dimensional, highly unsteady turbulent flow within turbine or compressor stages. The objective of this book is to present the fundamental principles of turbomachinery fluid-thermodynamic design process of turbine and compressor components, power generation and aircraft gas turbines in a unified and compact manner. The book provides senior undergraduate students, graduate students and engineers in the turbomachinery industry with a solid background of turbomachinery flow physics and performance fundamentals that are essential for understanding turbomachinery performance and flow complexes.   While maintaining the unifying character of the book structure in this second revised and extended edition all chapters have undergone a rigorous update and enhancement. Accounting for the need of the turbomachinery community, three chapters have been added, that deal with computationally relevant aspects of turbomachinery design such as boundary layer transition, turbulence and boundary layer.